Multiple Drugs Causing Severe Anemia in Infective Endocarditis - Singh, Ajit; N. Shetty, Prasad; Mohan Kumar Singh, Brij; Devasia, Tom (Cardiovascular & Haematological Disorders - Drug Targets, 2016)
Ceftriaxone and linezolid are commonly used antibiotics in infective endocarditis. Here we present a rare case of severe anemia caused by both the drugs via different mechanisms. Drugs have shown significant contribution in inducing anemia via hemolysis and bone marrow suppression in an infective endocarditis patient.
Keywords: Anemia